Academician V. H. Serheiev – Control System Designer, Founder of the Scientific and Design School, Honored Citizen of Kharkiv (on His 110th Birthday) - Elena Tverytnykova; Olena Voitiuk (Studia Historiae Scientiarum)
March 5, 2024 marks the 110th birthday of Volodymyr Hryhorovych Serheiev, an outstanding scientist, chief designer of control systems for strategic combat missiles, launch vehicles, spacecraft and transport modules of orbital complexes, Academician of the National Academy of Sciences of  Ukraine and an Honored Citizen of Kharkiv. Despite his significant scientific achievements in the field of rocket and space engineering, the silhouette of V. H. Serheiev is hardly reflected in the modern history of science.